Effect of nusinersen on pulmonary function in children with spinal muscular atrophy in the plateau region: A pilot study - Jicai Zhu; Xiaofang Chen; Haoke Sang; Minming Ma; Chunhui Tang (Heliyon)
Background: The drug nusinersen is applied to improve motor function in patients with spinal muscle atrophy (SMA). However, research on the effects of this treatment on lung function is lacking. Aim: To investigate the effect of nusinersen on lung function in children with SMA in the Plateau. Methods: A total of 20 patients with SMA (types 1, 2, or 3) who started nusinersen treatment at the Department of Pediatrics at Yunnan First People's Hospital from March 2022 and February 2024 were studied. A retrospective study was conducted to investigate changes in lung function parameters (including forced vital capacity, forced expiratory volume at 1 s, forced expiratory volume at 1 s/forced vital capacity, and peak expiratory flow) in patients with SMA treated with nusinersen. Results: 20 patients (13 male, 7 female; aged 5–16 years) were enrolled, including 2, 9, and 9 with SMA types 1, 2, and 3, respectively. The mean value of FVC % and FEV1/FVC % did not decrease further following nusinersen treatment in any patients. The mean value of FEV1% was 4.4 % and 5.0 % higher than before treatment in all patients (P = 0.03), and those with type 2 SMA (P = 0.04), respectively. The overall mean PEF % did not decrease any further after treatment. However, the average level in the type 2 group increased by 2.9 % (P = 0.03). Conclusion: Patients with SMA, particularly those classified as type 2, showed a trend of improvement in lung function following nusinersen treatment.